2018
DOI: 10.1038/s41467-017-02504-1
|View full text |Cite
|
Sign up to set email alerts
|

Tectonically-triggered sediment and carbon export to the Hadal zone

Abstract: Sediments in deep ocean trenches may contain crucial information on past earthquake history and constitute important sites of carbon burial. Here we present 14C data on bulk organic carbon (OC) and its thermal decomposition fractions produced by ramped pyrolysis/oxidation for a core retrieved from the >7.5 km-deep Japan Trench. High-resolution 14C measurements, coupled with distinctive thermogram characteristics of OC, reveal hemipelagic sedimentation interrupted by episodic deposition of pre-aged OC in the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
106
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(113 citation statements)
references
References 43 publications
(61 reference statements)
7
106
0
Order By: Relevance
“…This complements previous studies based on the composition of turbidites, which suggested earthquake-triggered remobilization of the upper 1-9 cm of slope sediments (McHugh et al, 2016;Moernaut et al, 2017). Furthermore, our results are in line with recent studies discussing the importance of earthquake shaking for transporting organic-rich surficial slope sediment to the hadal trench, forming an important contributor to the marine carbon cycle (Bao et al, 2018;Kioka et al, 2019;Mountjoy et al, 2018).…”
Section: Implications For Earthquake-triggered Sediment Transport Andsupporting
confidence: 92%
“…This complements previous studies based on the composition of turbidites, which suggested earthquake-triggered remobilization of the upper 1-9 cm of slope sediments (McHugh et al, 2016;Moernaut et al, 2017). Furthermore, our results are in line with recent studies discussing the importance of earthquake shaking for transporting organic-rich surficial slope sediment to the hadal trench, forming an important contributor to the marine carbon cycle (Bao et al, 2018;Kioka et al, 2019;Mountjoy et al, 2018).…”
Section: Implications For Earthquake-triggered Sediment Transport Andsupporting
confidence: 92%
“…Thus, the potential release from the Earth's interior and/or the carrion transported from these ecosystems by ocean currents may provide food to hadal fauna. Moreover, earthquakes and the steep slope enhance the deposition rate by importing the surrounding sediment into trenches (Bao et al, ; Glud et al, ). Amphipods living on the refractory OM in these redeposited sediments seems feasible thanks to the revelation of a special enzyme within them (Kobayashi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Hadal trenches (water depth > 6,000 m) are mainly characterized by high hydrostatic pressure, low temperatures, oligotrophy, frequent geological activity, and isolation from the anthrosphere (Bao et al, 2018;Jamieson et al, 2010;Somero, 1992). However, organisms there are more vibrant than expected despite the limited input of organic matter (OM) from primary production in the surface ocean (Glud et al, 2013;Jamieson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Hadal zones are generally located in oceanic trenches that are formed along plate boundaries by movement of oceanic plates, and thus experience episodic and/or regular landslides [5, 6]. These landslides cause downward transportation of surface sediments along with relatively fresh OM via the funnel effect of trench geomorphology [711]. Moreover, higher sedimentation rates and concentrations of subseafloor organic compounds in trench bottom sediments compared to neighboring abyssal sediments have been reported in multiple trench regions under oligotrophic and eutrophic oceans [4, 1114].…”
Section: Introductionmentioning
confidence: 99%